Peran Manajer dan Keterampilan Manajerial dalam Novel The Manager Karya Armala Mia Chuz - Yayu Budiarti; Resya Nazella Afrisca; Eva Dwi Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Managers are individuals who achieve set results or goals through collaboration with other people. This emphasizes the importance of a manager's ability to lead, coordinate, and motivate work teams. The aim of this research is to describe how to become a manager with the skills contained in the novel The Manager by Armala Mia Chuz. The type of research in this research is qualitative research. The data collection technique used is listening and collecting text data. The listening method is a way to obtain data by listening to the facts of the story and the problems that occur in the novel. The materials used to collect data came from novels that had been read. The results of the research explain the content of the novel The Manager, where becoming a manager must be accompanied by effort and learning from many people and experiences, and must have skills.